Construction of SSR Based Genetic Linkage Map and Identification of QTLs Conferring CMD Resistance in Cassava - Vidya, P.; Nair, Aswathy G. H.; Mohan, C.; Sreekumar, J.; Vijayan, Ambu (International Journal of Bio-resource and Stress Management, 2020)
Cassava mosaic disease (CMD) is one of the most devastating Gemini viral diseases that challenge the cassava production with great economic loss. Utilizing host plant resistance through marker assisted breeding is the best sustainable way to tackle this geminiviral disease. High disease severity and increasing yield loss demands the identification of new quantitative trait loci (QTLs) for CMD resistance. In the present study, an attempt was made to construct SSR based linkage map using bi-parental mapping population developed from a cross of cassava cultivars viz., MNga-1 and CI-732 and identified new QTLs using interval mapping. Thirteen CMD associated marker alleles were revealed through single marker analysis (SMA) and two new QTL regions were identified in linkage groups viz., chrom7 and chrom22 using composite interval mapping (CIM). An epistatic interaction viz., additive-dominant (AD) and dominant-additive (DA) between QTLs in 0.1cM and 60.4cM of chrom7 was identified using multiple interval mapping (MIM). The heritability of resistance viz., broad sense heritability (H2) and narrow sense heritability (h2) were found to be 93% and 15% respectively. The expected gain from breeding population was found to be 0.4.